PENGARUH KEPEMIMPINAN, PELATIHAN, DAN KOMPETENSI APARATUR TERHADAP IMPLEMENTASI ANGGARAN BERBASIS KINERJA SKPD DI LINGKUNGAN PEMERINTAH PROVINSI SUMATERA BARAT - Faridil Afrasy; Hasdi Aimon (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The purpose of research to obtain: 1) the influence of leadership and training  at Satuan Perangkat Kerja Daerah (SKPD) in the West Sumatra and 2) the influence of leadership, training and competence to the implementation of performance-based budgeting in SKPD in the West Sumatra. The results showed that: 1) the higher the value the leadership and training  will increase personal competences at SKPD in the Government of West Sumatra, and 2) the higher the value of leadership, training and competence of personnel in the performance-based budget eating SKPD in the West Sumatra government will be better. The results of the study recommends public policies to: 1) provide training, seminars, or training for management officials of local finance, 2) pay attention to the efficiency and accuracy in accordance with the objectives of financial management areas, and 3) leadership increase cooperation good with officers, supervision or control and delegate authority to officers who truly understand the tasks assigned.   Key Words : Leadership, training, competence, west sumatera